Aerogel for heavy metal ion adsorption and preparation method thereof
By preparing the benzoxazine aerogel with a Mannich alkali bridge structure, the problem of poor effect of aerogels in the prior art when dealing with complex water pollution is solved, and multiple rapid adsorption effects and good heat and acid resistance are achieved.
Patent Information
- Application Number
- CN202411952449.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Existing aerogel adsorbents have limited effects when dealing with complex water pollution, and it is difficult to efficiently remove multiple heavy metal ions at the same time.
By preparing benzoxazine aerogel containing a Mannich alkali bridge structure, the structure is used to form a complex with heavy metal ions, thereby achieving multiple rapid adsorption effects.
The prepared aerogel has a high specific surface area, strong adsorption properties, good heat and acid resistance, and can efficiently remove a variety of heavy metal ions in harsh environments, which is low in cost and renewable.
Smart Images

Figure CN119751964A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heavy metal ion adsorbents, and particularly relates to an aerogel for heavy metal ion adsorption and a preparation method thereof. Background Art
[0002] At present, with the rapid development of industrialization and economy of human society, environmental pollution is becoming more and more serious, among which heavy metal pollution is one of the major sources. Industrial wastewater and waste gas cause the generation of a large amount of waste, and the heavy metal ions in them enter the soil or water bodies through natural sedimentation, rainwater leaching and other channels, and enter the normal circulation ecosystem. After heavy metals enter the human body through various channels, they will accumulate in the human body and cause serious harm to human health. At present, the treatment methods of heavy metal wastewater mainly include: chemical precipitation, neutralization, biological method, membrane filtration and adsorption, among which the adsorption method has received widespread attention due to its high efficiency, recyclability and easy treatment.
[0003] In the adsorption method, the performance of the adsorbent is the decisive factor in removing heavy metal ions. Aerogel has the advantages of low density, high specific surface area and high porosity, and is a type of adsorbent material with broad application prospects. More importantly, the composition of polluted water is generally complex, and most traditional aerogels can only remove one of the pollutants, which greatly limits their practical application in adsorbing pollutants. Therefore, it is urgent to develop a new type of aerogel adsorbent material that is low-cost, renewable, and has multiple rapid adsorption effects. Summary of the invention
[0004] The purpose of the present invention is to provide an aerogel for heavy metal ion adsorption and a preparation method thereof. A benzoxazine monomer is first prepared, and then the benzoxazine monomer is ring-opened and polymerized by thermal activation to form a Mannich base bridge, which can form a complex with heavy metal ions to achieve the purpose of adsorption.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a method for preparing aerogel for heavy metal ion adsorption, comprising the following steps:
[0007] A phenolic compound, a primary amine compound and formaldehyde are mixed in a solvent to obtain a benzoxazine monomer suspension after reaction, and the upper solution is removed after standing;
[0008] The remaining part is firstly solidified in sections to obtain a polybenzoxazine wet gel, and then dried to obtain an aerogel for heavy metal ion adsorption; or the remaining part is firstly dried to obtain a polybenzoxazine aerogel precursor, and then solidified in sections to obtain an aerogel for heavy metal ion adsorption.
[0009] Preferably, the molar ratio of the phenolic compound, the primary amine compound and the formaldehyde is 0.5-41:1:2-82.
[0010] Preferably, the raw materials blended in the solvent further include a surfactant.
[0011] More preferably, the molar ratio of the phenolic compound, the surfactant, the primary amine compound and the formaldehyde is 0.5-41:0-19:1:2-82, and the amount of the surfactant is not zero.
[0012] Further preferably, the surfactant is poloxamer F127 and / or poloxamer F68. Since the preparation process of the aerogel in the present invention is to first obtain a benzoxazine monomer suspension, adding a surfactant is beneficial to obtaining an emulsion. Poloxamer is a high molecular nonionic surfactant and is easily soluble in ethanol and water. This type of surfactant can interact with the early oligomers and is more conducive to the preparation of a precursor emulsion.
[0013] Optionally, the phenolic compound includes one or more of resorcinol, diphenolic acid and tannic acid.
[0014] Among the phenolic compounds, the carboxyl groups in diphenolic acid and the large amount of phenolic hydroxyl groups on the surface of tannic acid are both helpful for the chelation of heavy metal ions by the prepared aerogel.
[0015] Optionally, the primary amine compound includes one or more of ethylenediamine, hexamethylenediamine, decanediamine, triethylenetetramine, tetraethylenepentamine and 3-amino-5-mercapto-1,2,4-triazole.
[0016] Optionally, the formaldehyde includes paraformaldehyde and / or formaldehyde aqueous solution.
[0017] Optionally, the solvent includes one or more of ethanol, water, dioxane, chloroform, toluene and tetrahydrofuran.
[0018] Preferably, the curing temperature gradient of the polybenzoxazine wet gel is 40°C / 30min, 50°C / 30min, 60°C / 1h, 70°C / 1h and 90°C / 3h, respectively.
[0019] Optionally, the drying of the polybenzoxazine wet gel includes normal pressure drying or vacuum drying; the normal pressure drying has a temperature of 50 to 70° C. and a time of 24 to 48 h; the vacuum drying has a temperature of 50° C. and a time of 24 h.
[0020] Preferably, the drying temperature of the polybenzoxazine aerogel precursor is 80° C. for 72 h; the temperature gradients of the segmented curing of the polybenzoxazine aerogel precursor are 140° C. / 2 h, 160° C. / 2 h, 180° C. / 2 h and 200° C. / 3 h, respectively.
[0021] The preparation process of the aerogel of the present invention is to first obtain a benzoxazine monomer suspension or emulsion, and then further solidify it to obtain a gel. Since the prepared aerogel is a high temperature resistant thermosetting polymer gel, the required curing temperature is relatively high. In order to avoid structural unevenness that may be caused by curing at high temperature, such as the generation of more and larger holes, it is necessary to cure in stages by gradually increasing the temperature to obtain a gel with a uniform internal structure.
[0022] The second technical solution of the present invention is to provide an aerogel for heavy metal ion adsorption prepared according to the above-mentioned method for preparing aerogel for heavy metal ion adsorption.
[0023] The third technical solution of the present invention is to provide an application of the above-mentioned aerogel for heavy metal ion adsorption in the adsorption of heavy metal ions.
[0024] The beneficial technical effects of the present invention are as follows:
[0025] The preparation method of the aerogel for heavy metal ion adsorption provided by the invention is simple, has a short experimental period and is low in cost.
[0026] The aerogel prepared by the present invention for heavy metal ion adsorption contains abundant heteroatoms (such as N, O, S, etc.), which can chelate with heavy metal ions to improve adsorption performance.
[0027] The aerogel prepared by the present invention for heavy metal ion adsorption has a large specific surface area, strong adsorption, little environmental pollution, and good heat resistance and acid resistance, and can be used in harsh environments such as high temperature and acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the infrared spectrum of the polybenzoxazine aerogel prepared in Example 1-5.
[0029] Figure 2 This is a graph showing the TGA test analysis results of the polybenzoxazine aerogel prepared in Examples 1-5.
[0030] Figure 3 This is a graph showing the acid resistance test analysis results of the polybenzoxazine aerogel prepared in Examples 1-5.
[0031] Figure 4 This is a scanning electron microscope image of the polybenzoxazine aerogel prepared in Example 1.
[0032] Figure 5 This is a scanning electron microscope image of the polybenzoxazine aerogel prepared in Example 2.
[0033] Figure 6 This is a scanning electron microscope image of the polybenzoxazine aerogel prepared in Example 3.
[0034] Figure 7 This is a scanning electron microscope image of the polybenzoxazine aerogel prepared in Example 4.
[0035] Figure 8 This is a scanning electron microscope image of the polybenzoxazine aerogel prepared in Example 5.
[0036] Fig. 9 This is a diagram showing the adsorption effect of the polybenzoxazine aerogel prepared in Examples 1-5 on various heavy metal ions. DETAILED DESCRIPTION
[0037] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0038] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0039] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0041] Example 1
[0042] (1) First, weigh 5.4 g of resorcinol, 2.5 g of poloxamer F127, 22.8 mL of anhydrous ethanol and 18 mL of deionized water into a 100 mL three-necked flask, set the temperature to 25°C, stir for 20 min, then add 0.156 g of hexamethylenediamine, continue stirring for 40 min, then quickly add 8.84 g of 37% formaldehyde solution, and after 10 min, add 0.6 g of tannic acid dissolved in 2.5 mL of deionized water, continue the reaction for 3 h, and bottle the resulting suspension and let it stand for 24 h;
[0043] (2) pouring out the supernatant in the glass bottle that has been left to stand for a long time in step (1), and then curing the mixture at 40°C / 30 min, 50°C / 30 min, 60°C / 1 h, 70°C / 1 h, and 90°C / 3 h to obtain a polybenzoxazine wet gel;
[0044] (3) The wet gel in step (2) was taken out and dried under vacuum at 50° C. for 24 h to obtain a polybenzoxazine aerogel, which was designated as RTH-1.
[0045] Example 2
[0046] (1) First, weigh 6.0 g of resorcinol, 2.5 g of poloxamer F127, 22.8 mL of anhydrous ethanol and 18 mL of deionized water into a 100 mL three-necked flask, set the temperature to 25 °C, stir for 20 min, then add 0.2 mL of triethylenetetramine (1.3 mol), continue stirring for 40 min, then quickly add 8.84 g of 37% formaldehyde aqueous solution, continue to react for 3 h, and bottle the resulting suspension and let it stand for 24 h;
[0047] (2) pouring out the supernatant in the glass bottle that has been left to stand for a long time in step (1), and then curing the mixture at 40°C / 30 min, 50°C / 30 min, 60°C / 1 h, 70°C / 1 h, and 90°C / 3 h to obtain a polybenzoxazine wet gel;
[0048] (3) The wet gel in step (2) was taken out and dried under vacuum at 50° C. for 24 h to obtain a polybenzoxazine aerogel, which was designated as RTH-2.
[0049] Example 3
[0050] (1) First, weigh 3.0 g of resorcinol, 7.8 g of diphenolic acid, 2.5 g of poloxamer F127, 22.8 mL of anhydrous ethanol and 18 mL of deionized water into a 100 mL three-necked flask, set the temperature to 30°C, stir for 20 min, then add 0.2 mL of triethylenetetramine (1.3 mol), continue stirring for 40 min, then quickly add 8.84 g of 37% formaldehyde aqueous solution, continue reacting at 50°C for 40 min, and bottle the resulting suspension and let it stand for 24 h;
[0051] (2) pouring out the supernatant in the glass bottle that has been left to stand for a long time in step (1), and then curing the mixture at 40°C / 30 min, 50°C / 30 min, 60°C / 1 h, 70°C / 1 h, and 90°C / 3 h to obtain a polybenzoxazine wet gel;
[0052] (3) The wet gel in step (2) was taken out and dried under vacuum at 50° C. for 24 h to obtain a polybenzoxazine aerogel, which was designated as RTH-3.
[0053] Example 4
[0054] (1) First, weigh 3.0 g of resorcinol, 7.8 g of diphenolic acid, 2.5 g of poloxamer F127, 22.8 mL of anhydrous ethanol and 18 mL of deionized water into a 100 mL three-necked flask, set the temperature to 30°C, stir for 20 min, then add 0.254 mL of tetraethylenepentamine (1.3 mol), continue stirring for 40 min, then quickly add 8.84 g of 37% formaldehyde aqueous solution, continue to react at 50°C for 40 min, and bottle the resulting suspension and let it stand for 24 h;
[0055] (2) pouring out the supernatant in the glass bottle that has been left to stand for a long time in step (1), and then curing the mixture at 40°C / 30 min, 50°C / 30 min, 60°C / 1 h, 70°C / 1 h, and 90°C / 3 h to obtain a polybenzoxazine wet gel;
[0056] (3) The wet gel in step (2) was taken out and dried under vacuum at 50° C. for 24 h to obtain a polybenzoxazine aerogel, which was designated as RTH-4.
[0057] Example 5
[0058] (1) First, weigh 1.1 g of resorcinol, 2.3 g of 3-amino-5-mercapto-1,2,4-triazole, 3.2 g of 37% formaldehyde aqueous solution and 20 mL of dioxane into a 100 mL three-necked flask, stir and dissolve at -10°C, continue the reaction for 1 hour after the dissolution is complete, and bottle the resulting suspension and let it stand overnight;
[0059] (2) The sample in step (1) was placed in an oven at 80°C for further reaction for 72 hours to obtain a polybenzoxazine aerogel precursor, and then cured at 140°C / 2h, 160°C / 2h, 180°C / 2h, and 200°C / 3h to obtain a polybenzoxazine aerogel, which was recorded as RTH-5.
[0060] The polybenzoxazine aerogels in Examples 1-5 were immersed in 800 mg / L FeCl3, K2CrO4, CuCl2, Pb(NO3)2, ZnCl2, SnCl2 and other solutions, respectively. After adsorption at room temperature for 24 h, the residual heavy metal ion concentration in the solution was determined by ultraviolet spectrophotometry, and then the heavy metal ion removal rate of the polybenzoxazine aerogel was determined.
[0061] Fe 3+ The determination method is as follows: first use hydroxylamine hydrochloride to 3+ Reduction to Fe 2+ Then use o-phenanthroline as a complexing agent with Fe 2+Generate a stable complex and measure its absorbance at 511nm, wherein o-phenanthroline is 0.5% (prepared with a little ethanol to dissolve), and hydroxylamine hydrochloride is 10%. Dilute 800mg / L FeCl3 solution 40 times, and take 0mL, 0.4mL, 0.8mL, 1.2mL, 1.6mL and 2mL of the diluted solution in 10mL centrifuge tubes and record them as 1-6, then add 0.2mL10% hydroxylamine hydrochloride solution, 0.4mL 0.5% o-phenanthroline solution, acetic acid-sodium acetate as buffer solution to adjust pH to about 6, and finally add deionized water to 10mL. 2-5 were then added with polybenzoxazine aerogel for adsorption for 24 hours, the solution after polybenzoxazine aerogel adsorption was diluted 40 times, and then 2 mL was taken from each sample as 7-11, 0.2 mL of 10% hydroxylamine hydrochloride solution, 1 mL of HAc-NaAc buffer solution, 0.4 mL of 0.5% o-phenanthroline solution were added, and finally deionized water was added to 10 mL. After shaking, the absorbance of samples 1-11 at 511 nm was measured on a UV spectrophotometer, and the absorbance of samples 1-6 at 511 nm and their corresponding concentrations were used as standard curves, and the standard curves were fitted to obtain a linear equation, and then the absorbance of samples 7-11 at 511 nm was substituted into the linear equation to calculate the concentration, and then the removal rate R (mg / g) was calculated according to the following formula:
[0062]
[0063] In formula (1-1): C0——metal ion concentration in the solution at the initial moment, mg / L;
[0064] C1——metal ion concentration in the solution after 24h adsorption, mg / L;
[0065] m——mass of polybenzoxazine aerogel, g;
[0066] v——volume of solution, L.
[0067] Cr 6+The determination method is as follows: 800 mg / L K2CrO4 solution was diluted 10 times, and 0 mL, 0.5 mL, 0.625 mL, 0.75 mL, 0.875 mL, and 1 mL of the diluted solution were taken in 10 mL centrifuge tubes, and were marked as No. 1-6, No. 2-5 were added to polybenzoxazine aerogel for adsorption for 24 h, and the K2CrO4 solutions after adsorption of the five polybenzoxazine aerogels in the embodiment were diluted 10 times and 1 mL was taken in 10 mL centrifuge tubes, and were marked as No. 7-11, and No. 1-11 samples were added with 5 mL 0.04 mol / L disodium ethylenediaminetetraacetic acid and acetic acid-sodium acetate were used as buffer solution to adjust the pH to about 6, and deionized water was added to make the volume 10 mL. The absorbance at 369 nm was measured within 15 min, and the absorbance of samples 1-6 at 369 nm and their corresponding concentrations were used as standard curves. The standard curves were fitted to obtain a linear equation, and then the absorbance of samples 7-11 at 369 nm were substituted into the linear equation to calculate the concentration. The calculation formula is consistent with formula (1-1).
[0068] Cu 2+ The determination method is as follows: 800 mg / L CuCl2 solution was diluted 100 times, and 0 mL, 2 mL, 2.5 mL, 3 mL, 3.5 mL, and 4 mL of the diluted solution were taken in 10 mL centrifuge tubes, and were marked as No. 1-6, No. 2-5 were added to polybenzoxazine aerogel for adsorption for 24 hours, and the five kinds of CuCl2 solutions adsorbed by polybenzoxazine aerogel in the embodiment were diluted 100 times and 3 mL were taken in 10 mL centrifuge tubes, and were marked as No. 7-11, and No. 1-11 samples were added with 4 mL 0.04 mol / L disodium ethylenediaminetetraacetic acid and acetic acid-sodium acetate were used as buffer solution to adjust the pH to about 6, and deionized water was added to make the volume 10 mL. The absorbance at 732 nm was measured within 15 min, and the absorbance of samples 1-6 at 732 nm and their corresponding concentrations were used as standard curves. The standard curves were fitted to obtain a linear equation, and then the absorbance of samples 7-11 at 732 nm was substituted into the linear equation to calculate the concentration. The calculation formula is consistent with formula (1-1).
[0069] Pb 2+The determination method is as follows: 800 mg / L Pb(NO3)2 solution was diluted 40 times, and 0 mL, 1 mL, 1.5 mL, 2 mL, 2.5 mL, and 3 mL of the diluted solution were taken in 10 mL centrifuge tubes, and were marked as No. 1-6, No. 2-5 were added to polybenzoxazine aerogel for adsorption for 24 hours, and the Pb(NO3)2 solutions after adsorption by the five polybenzoxazine aerogels in the embodiment were diluted 40 times and 2 mL were taken in 10 mL centrifuge tubes, and were marked as No. 7-11, and 0.28 mL of No. 1-11 samples were added. 0.003 mol / L xylenol orange solution and acetic acid-sodium acetate were used as buffer solution to adjust the pH to about 6, and deionized water was added to make the volume 10 mL. The absorbance at 524 nm was measured within 15 min, and the absorbance of samples 1-6 at 524 nm and their corresponding concentrations were used as standard curves. The standard curves were fitted to obtain a linear equation, and then the absorbance of samples 7-11 at 732 nm was substituted into the linear equation to calculate the concentration. The calculation formula is consistent with formula (1-1).
[0070] Sn 2+ The determination method is as follows: 800 mg / L SnCl2 solution was diluted 8 times, and 0 mL, 0.375 mL, 0.5 mL, 0.625 mL, 0.75 mL, and 0.875 mL of the diluted solution were taken in 10 mL centrifuge tubes, and were marked as No. 1-6, No. 2-5 were added to polybenzoxazine aerogel for adsorption for 24 h, and the SnCl2 solutions after adsorption of the five polybenzoxazine aerogels in the embodiment were diluted 8 times and 0.75 mL was taken in 10 mL centrifuge tubes, and were marked as No. 7-11, and No. 1-11 samples were added to Add 0.28mL 0.003mol / L xylenol orange solution and acetic acid-sodium acetate as buffer solution to adjust the pH to about 6, add deionized water to make up to 10mL, measure the absorbance at 490nm within 15min, and use the absorbance of samples 1-6 at 490nm and their corresponding concentrations as standard curves, and fit the standard curves to obtain a linear equation, and then substitute the absorbance of samples 7-11 at 732nm into the linear equation to calculate the concentration. The calculation formula is consistent with formula (1-1).
[0071] The infrared spectra of the polybenzoxazine aerogels prepared in Examples 1-5 are shown in Figure 1 ,from Figure 1 It can be seen that the vibration peak of the oxazine ring at 900-960 disappears, and the phenolic hydroxyl absorption vibration peak appears, indicating that the two curing methods provided by the present invention have successfully prepared polybenzoxazine aerogel.
[0072] The TGA test analysis results of the polybenzoxazine aerogel prepared in Examples 1-5 are shown in FIG. Figure 2 ,from Figure 2It can be seen that the weight loss of the five samples is not obvious below 250°C, indicating that each sample can exhibit good thermal stability in a high temperature environment below 250°C.
[0073] The acid resistance test analysis results of the polybenzoxazine aerogels prepared in Examples 1-5 are shown in Figure 3 , the samples were immersed in strong acid solutions of pH = 1 and pH = 3 for 24 hours, and the weight loss method was used to compare the effects of the strong acid solutions on the samples. The reduction ratio of the sample mass before and after immersion in the strong acid solution was calculated according to formula (1-2). Figure 3 It can be seen that the mass loss of the samples is within 8%, especially the mass loss rate of the sample in Example 5 is within 3%, and the samples show good acid resistance.
[0074]
[0075] In formula (1-2): m0 is the mass of the sample before immersion in strong acid solution, g;
[0076] m1——The mass of the sample after immersion in strong acid solution for 24 hours, g.
[0077] The scanning electron microscope image of the polybenzoxazine aerogel prepared in Example 1 is shown in Figure 4 .
[0078] The scanning electron microscope image of the polybenzoxazine aerogel prepared in Example 2 is shown in Figure 5 .
[0079] The scanning electron microscope image of the polybenzoxazine aerogel prepared in Example 3 is shown in Figure 6 .
[0080] The scanning electron microscope image of the polybenzoxazine aerogel prepared in Example 4 is shown in Figure 7 .
[0081] The scanning electron microscope image of the polybenzoxazine aerogel prepared in Example 5 is shown in Figure 8 .
[0082] from Figures 4 to 8 It can be seen that the polybenzoxazine aerogel prepared by the present invention presents a porous structure, which greatly increases the specific surface area of the aerogel.
[0083] The adsorption effect of polybenzoxazine aerogel prepared in Examples 1-5 on various heavy metal ions is shown in FIG. Figure 8 .
[0084] from Fig. 9 It can be seen that the polybenzoxazine aerogels prepared in Examples 1-5 have a strong affinity for Fe 3+ Cr 6+ , Cu 2+ , Pb 2+and Sn 2+ All of them have certain adsorption properties, especially for Sn 2+ The adsorption amount of Sn 2+ In addition, RTH-4 has the highest adsorption capacity for five heavy metal ions compared with other aerogels, which is due to the introduction of -COOH and more heteroatoms.
[0085] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing aerogel for heavy metal ion adsorption, characterized in that: The following steps are involved: A phenolic compound, a primary amine compound and formaldehyde are mixed in a solvent to obtain a benzoxazine monomer suspension after reaction, and the upper solution is removed after standing; The remaining part is firstly solidified in sections to obtain a polybenzoxazine wet gel, and then dried to obtain an aerogel for heavy metal ion adsorption; or the remaining part is firstly dried to obtain a polybenzoxazine aerogel precursor, and then solidified in sections to obtain an aerogel for heavy metal ion adsorption.
2. The method for preparing aerogel for heavy metal ion adsorption according to claim 1, characterized in that: The molar ratio of the phenolic compound, the primary amine compound and the formaldehyde is 0.5-41:1:2-82.
3. The method for preparing aerogel for heavy metal ion adsorption according to claim 1, characterized in that: The raw materials blended in the solvent also include a surfactant.
4. The method for preparing aerogel for heavy metal ion adsorption according to claim 3, characterized in that: The molar ratio of the phenolic compound, the surfactant, the primary amine compound and the formaldehyde is 0.5-41:0-19:1:2-82, and the amount of the surfactant is not zero.
5. The method for preparing aerogel for heavy metal ion adsorption according to claim 4, characterized in that: The surfactant is poloxamer F127 and / or poloxamer F68.
6. The method for preparing aerogel for heavy metal ion adsorption according to claim 1 or 3, characterized in that: The curing temperature gradients of the polybenzoxazine wet gel are 40°C / 30min, 50°C / 30min, 60°C / 1h, 70°C / 1h and 90°C / 3h, respectively.
7. The method for preparing aerogel for heavy metal ion adsorption according to claim 1 or 3, characterized in that: The polybenzoxazine aerogel precursor is dried at 80°C for 72 hours. The temperature gradients for the segmented curing of the polybenzoxazine aerogel precursor are 140°C / 2h, 160°C / 2h, 180°C / 2h and 200°C / 3h, respectively.
8. An aerogel for heavy metal ion adsorption obtained according to the method for preparing aerogel for heavy metal ion adsorption according to any one of claims 1 to 7.
9. Use of the aerogel for heavy metal ion adsorption according to claim 8 in the adsorption of heavy metal ions.
Citation Information
Patent Citations
Benzoxazine resin based carbon aerogel and a preparing method thereof
CN106082170A
Polybenzoxazine aerogel heat thermal insulation material and preparation method thereof
CN108690191A
Biomass mussel bionic polybenzoxazine containing catechol groups as well as synthesis method and application of biomass mussel bionic polybenzoxazine
CN113185661A
Polybenzoxazine aerogel and preparation method thereof
CN114015194A
High-temperature-resistant polybenzoxazine aerogel and preparation method thereof
CN116396477A